Síntese e Caracterização de Nanopartículas Semicondutoras com Estrutura tipo Núcleo/Casca CdSe/CdS obtidas por Rota Coloidal Aquosa - Fábio Pereira Ramanery (2012)
Nanoparticles of semiconductor materials with diameters of less than 10nm are particles called quantum dots (PQ's, English, quantum dots, QD's) and have unique size-dependent optical properties. The present FPs dimensions intermediate between the macro-molecules and the crystals and their optical properties, physical and chemical properties are distinct from the material presented in the form of extended solid. The effect of confinement in quantum dots allows for diverse applications in several areas of technological interest as optoelectronic devices, photovoltaic and biological markers in the biomedical area. The synthesis of nanoparticles with structure type core / shell (CS) for semiconductors, particularly semiconductor cadmium selenide (CdSe) and cadmium sulfide (CdS), among others, have been prepared by different methods, with an aqueous colloidalpromising route to not use toxic precursors in normal temperature and pressure compatible with biological systems. In this study were synthesized cores quantum dots with a structure NC-type semiconductor core CdSe and CdS aqueous colloidal route by using poly (vinyl alcohol) as a stabilizer. We investigated the changes in optical properties of CdSe PQs for the formation of different thicknesses of CdS shell. The property of luminescence, formation and evaluation of the dispersion particle size was backed by photoluminescence (PL) and characterized by spectroscopy ultraviolet-visible (UV-vis). The morphological characteristics were investigated by transmission electron microscopy (TEM) and chemical evaluation of the particles with core / shell structure was analyzed by EDS.